Symptomatic Premature Ventricular Contractions in Vasovagal Syncope Patients: Autonomic Modulation and Catheter Ablation - Zheng, Lihui; Sun, Wei; Qiao, Yu; Hou, Bingbo; Guo, Jinrui; Killu, Ammar; Yao, Yan (Frontiers in Physiology, 2021)
Introduction: There has been limited reports about the comorbid premature ventricular contractions (PVCs) and vasovagal syncope (VVS). Deceleration capacity (DC) was demonstrated to be a quantitative evaluation to assess the cardiac vagal activity. This study sought to report the impact of autonomic modulation on symptomatic PVCs in VVS patients. Methods and Results: Twenty-six VVS patients with symptomatic idiopathic PVCs were consecutively enrolled. Identification and catheter ablation of left atrial ganglionated plexi (GP) and PVCs were performed in 26 and 20 patients, respectively. Holter 24h-electrocardiogramss were performed before and after the procedure to evaluate DC and PVCs occurrence. Eighteen patients were subtyped as DC-dependent PVCs (D-PVCs) and 8 as DC-independent PVCs groups (I-PVCs). In D-PVCs group, circadian rhythm of hourly PVCs was positively correlated with hourly DC (P<0.05) while there was no correlation in I-PVCs group (P>0.05). 53 GPs with positive vagal response were successfully elicited (2.0±0.8 per patient). PVCs failed to occur spontaneously nor to be induced in 6 patients. In the remaining 20 patients, PVCs foci identified were all located in the ventricular outflow tract region. Post-ablation DC decreased significantly from baseline (P <0.05). During mean follow-up of 10.64 ± 6.84 months, syncope recurred in 1 patient and PVCs recurred in another. PVCs burden of the 6 patients in whom neither catheter ablation nor antiarrhythmic drugs were applied demonstrated a significant decrease during follow-up (P=0.037). Conclusion: Autonomic activities were involved in the occurrence of symptomatic idiopathic PVCs in some VVS patients. D-PVCs might be facilitated by increased vagal activities. Catheter ablation of GP and PVCs foci may be an effective, safe treatment in patients with concomitant VVS and idiopathic PVCs.